A Novel Method for Long-Term Analysis of Lactic Acid and Ammonium Production in Non-growing Lactococcus lactis Reveals Pre-culture and Strain Dependence - Nugroho, Avis Dwi Wahyu; Kleerebezem, Michiel; Bachmann, Herwig (Frontiers in Bioengineering and Biotechnology, 2020)
In various (industrial) conditions, cells are in a non-growing but metabolically active state in which de-novo protein synthesis capacity is limited. The production of a metabolite by such non-growing cells is dependent on the cellular condition and enzyme activities such as the amount, stability, and degradation of the enzyme(s). For industrial fermentations in which the metabolites of interest are mainly formed after cells enter the stationary phase, the investigation of prolonged metabolite production is of great importance. However, current batch model systems do not allow prolonged measurements due to metabolite accumulation driving product-inhibition. Here we developed a protocol that allows high-throughput metabolic measurements to be followed in real-time over extended periods (weeks). As a validation model, sugar utilization and arginine consumption by a low density of translationally-blocked Lactococcus lactis was designed in a defined medium. In this system L. lactis MG1363 was compared with its derivative HB60, a strain described to achieve higher metabolic yield through a shift towards heterofermentative metabolism. The results showed that in a non-growing state HB60 is able to utilize more arginine than MG1363, and for both strains the decay of the measured activities were dependent on pre-culture conditions. During the first 5 days of monitoring a ~25-fold decrease in acidification rate was found for strain HB60 as compared to a ~20-fold decrease for strain MG1363. Such measurements are relevant for the understanding of microbial metabolism and for optimizing applications in which cells are frequently exposed to long-term suboptimal conditions such as microbial cell factories, fermentation ripening, and storage survival.